High‐strength poly(para‐phenylene) as an orthopedic biomaterial. Issue 9 (16th October 2013) - Frick, Carl P.; DiRienzo, Amy L.; Hoyt, Anthony J.; Safranski, David L.; Saed, Mohand; Losty, Eric J.; Yakacki, Christopher M.
Abstract Poly(para‐phenylene) (PPP) exhibits exceptional mechanical strength, stiffness, toughness, and chemical inertness, although it is not currently used in any biomedical applications. The purpose of this study is to serve as a preliminary investigation into the potential of PPP as a biomaterial in orthopedic load‐bearing applications. Nuclear magnetic resonance (NMR) analysis confirmed a polymer structure composed of an aromatic backbone and side groups. Tensile PPP specimens along with samples from several other polymers often used for orthopedic applications were elongated to failure after being soaked in phosphate buffered saline (PBS) for 1 h, 1 day, 1 week, 2 weeks, 1 month, and more than 1 year. Results showed that PBS absorption of the PPP plateaued at 1 week at values of ∼0.7 wt % and remained within one standard deviation when soaked for over 1 year. PBS absorption did not affect elastic modulus (5.0 GPa), yield strength (141 MPa), fracture strength (120 MPa) and strain‐to‐failure (17%) more than one standard deviation. Zero‐to‐tension fatigue testing established an endurance limit of approximately 35 MPa, which was relatively insensitive to frequency (1–10 Hz). Eagle's minimum essential medium (MEM) elution assay with fibroblasts confirmed that the PPP was noncytotoxic. Relative to other polymers used for load‐bearing biomedical applications, PPP displays promising mechanical properties that remain stable in aqueous solution. Lastly, prototype PPP and polyetheretherketone (PEEK) bone plates were manufactured and tested, with the PPP plate showing a 38% higher maximum tensile load before failure. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3122–3129, 2014.